The Relationship between Clinical Governance and Hospital Performance: Evidence of Ardabil - habib ebrahimpour; hassan khalili; Mohammad pourali (Tehran University of Medical Sciences, 2014)
In many countries, different methods and tools for improving the quality of health cares have been used. Among these methods, the NHS clinical governance provided by the NHS British government as a strategy to enhance the quality of clinical cares was introduced in 1998. Clinical governance both responsibilities for maintain the current level of cares and improving the quality of future care are emphasized. Materials & Methods: The aim of this study was to investigate the relationship between clinical governance and organizational performance of hospitals in Ardabil. The research is an applied one questionnaire is used to collecting data. The population comprises patients, doctors employees and hospitals managers of Ardabil 180 were selected as the sample. To investigate the hypothesis test, correlation and regression analysis were used. Results: According to data, there is a significant relationship between organizational performance and clinical governance. On the other hand, the results of F test showed meaningful level for the components of %99, so we can use linear regression. Furthermore, the coefficient of all the components of clinical governance has a positive and significant effect on performance. Among the components of clinical governance, clinical audit component has %163 of the minimum amount, and staff management component 908 percent has the most effect on hospital performance. Conclusion: According to the results, are considered essential patient's engagement in treatment, the use of information and patients' family's experiences to provide more services to patients, credit allocation for staff training and staff expertise in the field of employees training.